Numerical Simulation of the Tar Mist and Dust Movement Process in a Low-Temperature Dry Distillation Furnace. (2nd March 2020) - Zhang, Qiuli; Hui, Xiangrong; Yan, Long; Luo, Min; Feng, Wenru; Zhou, Jun; Lan, Xinzhe
Abstract : In the low-temperature dry distillation of low-rank coal, the important liquid product of coal tar is produced, but its quality and utilization rate are degraded by entrained dust. The movement of coal tar and dust in the furnace is a key factor in causing particles such as dust to mix with coal tar. Therefore, the Euler–Lagrangian method is used to simulate the two-phase motion process of gas, tar, and dust in a furnace. By considering the effects of tar particle size, dust particle size, gas velocity, tar density, and dust density, the motion process mechanism is revealed, enabling the dust content in coal tar to be reduced and the quality improved. The results indicate that tar particles with sizes less than 0.20 mm can be removed from the furnace by gas, and the smaller the particle size is, the shorter the time required for removal. Dust particles greater than 0.18 mm in size cannot be completely removed from the furnace. As the gas velocity increases, the time required for complete removal of the tar mist and dust gradually decreases. When the speed is 0.70 m/s, all tar mist is removed, although some particles remain. Tar mist with a density of more than 900 kg/m 3 can be extensively removed, but dust with a density of more than 1400 kg/m 3 is difficult to remove and remains in the furnace. Finally, particle size distribution experiments in the product were conducted to verify the accuracy of the numerical simulation.